2014
DOI: 10.1121/1.4868371
|View full text |Cite
|
Sign up to set email alerts
|

Auditory detection of ultrasonic coded transmitters by seals and sea lions

Abstract: Ultrasonic coded transmitters (UCTs) are high-frequency acoustic tags that are often used to conduct survivorship studies of vulnerable fish species. Recent observations of differential mortality in tag control studies suggest that fish instrumented with UCTs may be selectively targeted by marine mammal predators, thereby skewing valuable survivorship data. In order to better understand the ability of pinnipeds to detect UCT outputs, behavioral high-frequency hearing thresholds were obtained from a trained har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Similarly, tagged predator species may experience a decrease in foraging success. Acoustic tags are becoming more widely used on sharks [ 30 32 ] and could make them more detectable by prey species such as seals [ 16 ]. Even recently published reports of acoustically tagged seals meeting at sea [ 33 ] could be caused by a tag attraction effect, as the tags used produced sounds similar to the fish tags used in the area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, tagged predator species may experience a decrease in foraging success. Acoustic tags are becoming more widely used on sharks [ 30 32 ] and could make them more detectable by prey species such as seals [ 16 ]. Even recently published reports of acoustically tagged seals meeting at sea [ 33 ] could be caused by a tag attraction effect, as the tags used produced sounds similar to the fish tags used in the area.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study, sensitivity thresholds for a Vemco 69 kHz fish tag signal were measured and used to estimate detection distances for a harbour seal ( Phoca vitulina ) and California sea lion ( Zalophus californianus ). Both species were found to be capable of detecting the signal (source level of 165 dB re 1 µPa) at simulated distances of greater than 200 m [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following data collection for Cook et al ( 2013 ), Ronan received intermittent “practice” sessions (typically no more than one per week) with familiar simple stimuli and several novel musical stimuli. During this time, Ronan also participated in several other cognitive and perceptual studies unrelated to rhythm (Reichmuth et al, 2013 ; Cunningham et al, 2014a , b ; Cook et al, 2015 ; Cunningham and Reichmuth, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, 'association studies' have not revealed evidence of predation by pinnipeds on any fish species and detection rates have generally been quite low. Recent work has shown that harbor seals in particular can hear the sound generated by Vemco 69 kHz tags (Cunningham et al 2014), and they can learn to associate the sound from the tags with food in a laboratory setting. This raises the question of whether the sound of the tag rings a 'dinner bell' that puts tagged fish at greater risk of predation (Stansbury et al 2015).…”
Section: Introductionmentioning
confidence: 99%